Pathologic study of a fatal case of dengue-3 virus infection in Rio de Janeiro, Brazil - Basílio-de-Oliveira,C.A. (2005)
Dengue hemorrhagic fever (DHF) is a severe febrile disease, characterized by abnormalities in hemostasis and increased vascular permeability, which in some cases results in hypovolemic shock syndrome and in dengue shock syndrome. The clinical features of DHF include plasma leakage, bleeding tendency and liver involvement. We studied the histopathological features of a fatal case of dengue-3 virus infection. The patient, a 63-year old male, presented with an acute onset of severe headache, myalgia and maculopapular rash. Tissue fragments (liver, spleen, lung, heart, kidney and lymph nodes) were collected for light microscopy studies and stained by standard methods. Histopathology revealed severe tissue damage, caused by intense hemorrhage, interstitial edema and inflammation. Some tissue sections were also processed with the immunoperoxidase reaction, which revealed the dengue viral antigen. Dengue-3 virus was isolated and identified with electron microscopy in a C6/36 cell culture inoculated with the patient's serum. Viral particles were detected in the infected cell culture.